2010
DOI: 10.1002/anie.201006881
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Functionalized Cyclohexenone Rings: Rhodium‐Catalyzed 1,3‐Acyloxy Migration and Subsequent [5+1] Cycloaddition

Abstract: Lead Rh‐ole: Highly substituted cyclohexenones were prepared from cyclopropyl‐substituted propargyl esters by using a [{Rh(CO)2Cl}2] catalyst. This metal catalyst promoted the 1,3‐acyloxy migration of propargyl esters and a subsequent [5+1] cycloaddition of the resulting allenylcyclopropanes in the presence of CO with high regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 89 publications
0
40
1
1
Order By: Relevance
“…8,9 We examined the regioselectivity for the cleavage of the cyclopropane ring and found that the C-C bond adjacent to an electron-rich aryl group or away from a quaternary carbon was selectively cleaved. 8,10 This provided the basis for the proposed regioselective [5+1] cycloaddition of cyclopropanes 5 or 8 .…”
mentioning
confidence: 99%
“…8,9 We examined the regioselectivity for the cleavage of the cyclopropane ring and found that the C-C bond adjacent to an electron-rich aryl group or away from a quaternary carbon was selectively cleaved. 8,10 This provided the basis for the proposed regioselective [5+1] cycloaddition of cyclopropanes 5 or 8 .…”
mentioning
confidence: 99%
“…Moreover, both of these cycloadditions involve a rhodium-catalyzed 1,2-acyloxy migration of propargyl esters which was reported in 1984 [159,160]. With some elegant work in this field [161][162][163], cyclopentenones can also be produced with the use of rhodium catalyst [Rh (COD)Cl] 2 (Scheme 51). Here, the acyloxy group in the propargyl ester starting material not only eliminates the need for the preformation of allenes but also provides a useful handle for further selective functionalization of the cyclopentenone products.…”
Section: %mentioning
confidence: 94%
“…We have previously shown that [{Rh(CO) 2 Cl} 2 ] is an efficient catalyst for the 1,3-acyloxy migration of propargyl esters. [11] Indeed, our preliminary study showed that product 9 could be obtained in 30-40 % yield with the catalyst [{Rh(CO) 2 Cl} 2 ]. Since this transformation has been carried out with the catalyst PtCl 2 , no further optimization was conducted.…”
Section: (B)mentioning
confidence: 99%
“…[10] We recently found that [{Rh(CO) 2 Cl} 2 ] was able to catalyze the 1,3-acyloxy migration of propargyl esters in the synthesis of functionalized cyclohexenones. [11] The combination of this novel reactivity of Rh I in promoting acyloxy migration and its well-known capability to undergo facile oxidative addition, migratory insertion, and reductive elimination may offer many opportunities for the design of new reactions. We envisioned that a conceptually new approach to seven-membered rings was possible if intermediate 6 in the Rautenstrauch rearrangement could be intercepted by a tethered alkyne in a [5+2] cycloaddition under rhodium catalysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation